53 A Rare Malignant Lesion of the Jaws. (12th October 2021) - Patel, V
Abstract: Introduction: Primary intraosseous carcinoma (PIOC) of the jaw is an incredibly rare lesion with approximately 200 cases reported in the literature. PIOC are mostly asymptomatic incidental radiographic findings and present as poorly-defined, non-corticated radiolucencies often with root resorption and cortical perforation. Prognosis is considered poor and best predicted by histological grade. Case report: A gentleman in his 50s presented to his dentist with a draining sinus from his LR6 tooth. A radiograph revealed a non-corticated radiolucency localised to the distal root of the LR6. 7 months later, he returned with pain and mobility of the LR7. Another radiograph revealed a non-corticated radiolucency from around the distal root of the LR6 extending to the LR8. Urgent biopsy of the mandibular bone was arranged by the oral and maxillofacial surgery team. Histopathology revealed the lesion was likely a benign squamous odontogenic tumour. However, it was not possible to exclude a well-differentiated squamous cell carcinoma. Correlation of clinical findings, imaging and multidisciplinary team discussion was recommended. Following the MDT meeting, excision of the bony lesion was undertaken. Histopathology this time returned as primary intraosseous carcinoma NOS T4N0M0, thought to have arisen from a radicular cyst associated with the LR6/7. The treatment was right segmental mandibulectomy, fibular free flap, selective neck dissection (I-III) and adjuvant radiotherapy. Conclusions: This case highlights how subtle radiographic features can represent malignancy in lesions appearing cystic at first. Although rare, clinicians should be aware of PIOC as a differential diagnosis when presented with radiographic features which could represent malignancy.